An experimental study to assess the best maneuver when using a reverse side-bevel histology needle for EUS-guided fine-needle biopsy - Yamabe, Akane; Irisawa, Atsushi; Shibukawa, Goro; Hoshi, Koki; Fujisawa, Mariko; Igarashi, Ryo; Abe, Yoko; Imbe, Koh (Endoscopy International Open, 2016)
Background and study aims: Recently, ProCore™ was developed as an endoscopy ultrasound (EUS)-guided histology needle designed to address several current limitations of EUS-guided fine-needle aspiration (FNA). Nevertheless, tissue yield with the ProCore™ is not consistent. No standard technique has been established. This experimental study was conducted to ascertain the best maneuver when using the ProCore™.Patients and methods: We performed fine-needle aspiration and biopsy (FNAB) with a 22-gauge (G) ProCore™ using chicken tenderloin and liver. Six methods were used, with two needle movement techniques (natural speed and whipping back) and three negative pressures (no suction (NS), slow pull (SP), and 10-mL suction).Results: In cases using the “natural speed” technique, a significant difference in tissue yield was found with suction pressures in both tenderloin and liver (P < 0.0001, P = 0.0079). In cases using the “whipping back” technique, for the tenderloin, no significant difference in tissue yield was found for NS vs. SP (P = 0.0596), however, a significant difference was found for SP vs. 10-mL suction (P < 0.0001) and for NS vs. 10-mL suction (P < 0.0001). For the liver, a significant difference was found among suction pressures (P = 0.0079). Comparing “natural speed” with “whipping back” using the tenderloin, no significant difference in tissue yield was found with NS and 10 mL of pressure (P = 0.1126, P = 0.0718), but a significant difference was found with SP (P = 0.0028). Regarding the liver, no significant difference was found based upon suction pressure (NS P = 0.1508; SP P = 0.0873; 10 mL P = 0.6667).Conclusions: EUS-FNAB using ProCore™ can be performed with negative pressure with any needling technique. Although ProCore™ has a reverse side-bevel, results in using it with a whipping-back technique were inconclusive.